Газогідродинамічні вимірювальні перетворювачі на складених дросельних елементах - Пістун, Євген; Леськів, Галина (Видавництво Національного університету «Львівська політехніка», 2002)
Сontains the principles of modelling of gashydrodynamical throttle measuring converters and systems. Generalized models of measuring converters built at one and composite throttle elements are presented.